Migraine And Pregnancy: What Should We Know - Restu Susanti; Syamel Muhammad (Andalas Obstetrics And Gynecology Journal, 2020)
Migraine is a common headache characterized by unilateral throbbing-like headache and pulsating in nature and sometimes associated with aura. Migraine is a disabling disorder that among adults is more prevalent among women than men. It is primary headache that is often found in pregnancy. Migraine is a common disorder in women of childbearing age, and usually requires pharmacological treatment. Migraine can be considered an important risk factor for hypertensive and vascular diseases during pregnancy. Migraine therapy in pregnancy is very challenging, it must taken into a consideration about the health of the mother and fetus.  Several effective antimigraine medications are reasonably safe for use by pregnant and breastfeeding women. Prophylactic theraphy should be given to patient with recurrent migraine attacks in pregnancy. Nonpharmacological strategies are always first-line treatment options for mild migraine, and should also be used complementarily whenever pharmacological treatment is required. Women with migraine should be offered periconceptional counselling to promote a safe and healthy pregnancy. Keywords: migraine; pregnancy; therapy